1985
DOI: 10.1111/j.1469-8137.1985.tb02795.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergism Between Calcium Ions and Abscisic Acid in Preventing Stomatal Opening

Abstract: The inhibition of stomatal opening in Commelina communis L. by abscisic acid (ABA) appears to be dependent on the availability of calcium ions. Incubation of epidermal strips in 10"° mol m~^ ABA had little effect in the absence of calcium, and a factorial experiment showed a highly significant calcium x .^BA interaction. The effect of calcium appeared to be on the later stages of the opening process, and might have been the result of an inhibition of potassium uptake by the guard cells. There was no detectable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
86
1
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(95 citation statements)
references
References 42 publications
(34 reference statements)
7
86
1
1
Order By: Relevance
“…(i) Increasing concentrations of external Ca 2 known to trigger stomatal closure under white light (Allen et al, 2001;DeSilva et al, 1985;Gilroy et al, 1990) classically induced stomatal closure in Ws-2 plants ( Figure 1b, closed circles), but had only a negligible effect on stomata of mrp5-1 plants ( Figure 1b, open squares).…”
Section: Resultsmentioning
confidence: 99%
“…(i) Increasing concentrations of external Ca 2 known to trigger stomatal closure under white light (Allen et al, 2001;DeSilva et al, 1985;Gilroy et al, 1990) classically induced stomatal closure in Ws-2 plants ( Figure 1b, closed circles), but had only a negligible effect on stomata of mrp5-1 plants ( Figure 1b, open squares).…”
Section: Resultsmentioning
confidence: 99%
“…These factors may explain why after only 1 h of incubation no relationship was observed between the Ca^* concentration in the medium and stomatal aperture. Nevertheless, the presence of calcium in the apoplast appears to be essential for the promotion of closure either by darkness or by ABA (Schwartz, 1985;Atkinson et al, 1989) and concentrations above O'l mol m~^ can themselves cause stomatal closure in the light (De Silva et al, 1985), Although the relationship between apoplastic and cj'tosolic Ca^* is probably less straightforward than for K*, there is no doubt that increasing apoplastic Ca^* causes closure of open stomata. Schwartz (1985) found that having pre-incubated detached leaves of C. communis in tap water for 2 h, subsequent incubation of abaxial epidermal strips in 1 mol m~^ CaCl, reduced aperture to < 90%.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data have reported increased stomatal opening in C. communis in response to increasing K* concentration (Travis & Mansfield, 1979) and a reduction in opening in response to increasing Ca^+ concentration (De Silva, Hetherington & Mansfield, 1985;Mansfield, Hetherington & Atkinson, 1990). Here we have found that, starting with open stomata, partial closure occurred in KCl concentrations of up to 50 mol m"^.…”
Section: Discussionmentioning
confidence: 99%
“…DeSilva et al, 1985) had suggested that there was a calcium requirement during ABA induced stomatal closure and that an increase in cytosolic free calcium ions might act to trigger the intraceliular machinery responsible for the reduction in guard cell turgor (see Mansfield et al, 1990). Recently, Gehring et al (1990) have demonstrated that application of ABA increased the concentration of free calcium ions in the cytosol of a number of tissues.…”
Section: Stomatal Closurementioning
confidence: 99%